Outpatient use of antibiotics in the Republic of Srpska: 2019 vs. 2020 - Stoisavljević Šatara, Svjetlana; Stojaković, Nataša; Golić Jelić, Ana; Djermanović, Mirjana; Škrbić, Ranko (Archives of Pharmacy, 2022)
COVID-19 disease caused by the SARS-CoV-2 virus, since December 2019, was being treated with a variety of antivirals, antibiotics, and antifungals. This study aims to analyze the outpatient use of antibiotics in the Republic of Srpska during the first year of COVID-19 pandemic. A pharmacoepidemiologic analysis in the Republic of Srpska (Srpska) was performed from 2019 to 2020, based on drug utilization data obtained from the Public Health Institute (PHI). Drug utilization analysis was undertaken using the ATC (Anatomical Therapeutic Chemical classification)/DDD (Defined Daily Dose) methodology, which is the internationally accepted methodology for measuring medicine utilization within and across populations. DDDs were defined as the amount of drug most used in adults for the most common indication. Data on outpatient antibiotic utilization were expressed in DDD/1,000 inhabitants/day (DIDs) for comparative purposes. Utilization of antibiotics in 2020 compared to 2019 had increased significantly for antibiotics ATC groups with highest DIDs in Srpska - J01C (61.31%), J01D (121.4%) and J01F (55.85%). There has been decrease in utilization for J01E (16,8%), J01X (17.13%) and JO1G (24.31%), thus these were the J01 groups with lowest DIDs in Srpska. Antibiotics should not be used as a means of preventions or treatment for SARS-CoV-2 virus unless bacterial co-infection was present. Further research is needed to evaluate immediate and long-term impact of antibiotic prescribing trends on specific antibiotic groups closely associated with increased resistance.